Bhāratavidyā-ratnaśrīḥ = Gems of Indology - Kulaśreṣṭha, Suṣamā (Pratibha Prakashan, 2010)
cascade 1. Dharmaśāstra-nirjharī -- cascade 2. Vyākaraṇaśāstra-nirjharī -- cascade 3. Nyāyaśāstra-nirjharī -- cascade 4 . Sarvadarśana-nirjharī